Predictive value of pulmonary function testing in the evaluation of pulmonary hypertension in sarcoidosis - Jose, Arun (Sarcoidosis Vasc Diffuse Lung Dis, 2018)
Background: In sarcoidosis patients, pulmonary hypertension (PH) is associated with significant morbidity and mortality. Early identification of sarcoidosis-associated pulmonary hypertension (SAPH) has substantial clinical implications. While a number of pulmonary function testing (PFT) variables have been associated with SAPH, the optimal use of PFT’s in screening for SAPH is unknown. Objectives: To examine the predictive value of PFT’s for echocardiographic PH in a cohort of sarcoidosis patients. Methods: We conducted a retrospective cohort study of patients with sarcoidosis from a single center over a period of five years. All consecutive adult patients with a diagnosis of biopsy-proven sarcoidosis (determined by review of the medical chart) who underwent PFT and echocardiographic testing were included. Echocardiographic risk of PH (either intermediate or high) was determined by the presence of echocardiographic PH signs and tricuspid regurgitant jet velocity. Data analysis was performed using multivariate logistic regression analysis with least absolute shrinkage and selection operator. Results: Of the 156 patients included in the study, 42 (27%) met the criteria for echocardiographic PH. Roughly equal proportions met the criteria for intermediate risk (45%) as did for high risk of PH (55%). The percent predicted of diffusion capacity for carbon monoxide (%DLCO) and forced vital capacity (%FVC) were predictive of echocardiographic PH. No other PFT variables outperformed these two markers, and the incorporation of additional PFT variables failed to significantly enhance the model. Conclusions: The %FVC and %DLCO emerged as being predictive of echocardiographic PH in this cohort of biopsy-proven sarcoidosis patients. Potentially reflecting the multifactorial pathogenesis of PH in sarcoidosis, incorporation of other PFT variables failed to enhance screening for PH in this population. (Sarcoidosis Vasc Diffuse Lung Dis 2018; 35: 308-316)